2010
DOI: 10.1063/1.3293445
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure of self-assembled InGaAs/GaAs quantum rings studied by capacitance-voltage spectroscopy

Abstract: Self-assembled InGaAs quantum rings, embedded in a GaAs matrix, were investigated using magneto-capacitance-voltage spectroscopy. The magnetic-field dispersion of the charging energies exhibits characteristic features for both the first and second electron, which can be attributed to a ground state transition from l=0 into l=−1, and a ground state transition from l=−1 into l=−2, respectively. Furthermore, using a combination of capacitance-voltage spectroscopy and one-dimensional numerical simulations, the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 15 publications
4
36
0
Order By: Relevance
“…Only using the geometry followed from Eq. (8) we reproduce result of (Lei et al, 2010), as is shown in Fig. 12.…”
Section: Experimental Data For Inas/gaas Qr and The Effective Modelsupporting
confidence: 76%
See 4 more Smart Citations
“…Only using the geometry followed from Eq. (8) we reproduce result of (Lei et al, 2010), as is shown in Fig. 12.…”
Section: Experimental Data For Inas/gaas Qr and The Effective Modelsupporting
confidence: 76%
“…The obtained geometry with the parameters m * and  from (Lei et al, 2010) is shown in Fig. 11 (Geometry 2); m *=0.067 0 m and  =15 meV.…”
Section: Experimental Data For Inas/gaas Qr and The Effective Modelmentioning
confidence: 99%
See 3 more Smart Citations